An Politicization of the Indonesian Armed Forces (TNI) Regarding ABRI’s Dual Function and Civilian Supremacy: Civilian Supremacy - Faonaso Harefa; Sovian Aritonang; Asep Adang Supriyadi; Cecilia F. Harsono (UIN Sunan Gunung Djati, 2025)
This study aims to analyze the relationship between the revision of Law Number 34 of 2004 and the issue of the return of ABRI's dual function and civil supremacy in the context of Indonesian democracy and reform. The mixed methods approach with SEM PLS-4 and NVivo 12 analysis is used to achieve that goal. The results of the analysis using NVivo 12 showed that ABRI's dwifunction would not return and civil supremacy was maintained because, legally, the TNI remained focused on its role as a tool of national defense. The civil government, through the Parliament and public supervision, has full authority to oversee the TNI so that the TNI still maintains its tested neutrality. The results of the SEM PLS-4 analysis show that the TNI Law's political variable on the issue of ABRI's dual function and civilian supremacy has a statistically significant effect, with a T-statistic value of 5.073 and P-value of 0.000 and a large effect on the model (F-square 0.489). The contribution of this research is to provide an understanding of the importance of a balance between freedom of opinion, politics, and the interests of national defense as a system that supports each other in the post-reform era, as well as in facing the challenges of reform and hybrid warfare towards Indonesia Gold Indonesia 2045. The limitations of this study lie in a limited time, which affects the depth of analysis and data scope so as to limit the perfection of the results of the research as a whole.